2001
DOI: 10.1002/ajim.10022
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk, silica exposure, and silicosis in Chinese mines and pottery factories: The modifying role of other workplace lung carcinogens*

Abstract: Our results suggest that, among silica-exposed Chinese workers, numerous occupational and non-occupational risk factors interact in a complex fashion to modify lung cancer risk. Future epidemiological studies on silica and lung cancer should incorporate detailed information on exposure to other workplace lung carcinogens, total respirable dust, and on surface size and age of silica particles to understand whether and to what extent they affect the carcinogenic potential of silica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Together with other recent reports, including experimental and epidemiological data evaluations [Chan et al, 2000;Hessel et al, 2000;Soutar et al, 2000;Carta et al, 2001;Cocco et al, 2001], the present study provides additional information of interest to further evaluate the association between silica and lung cancer [IARC, 1997;Steenland et al, 2001].…”
Section: Discussionmentioning
confidence: 74%
“…Together with other recent reports, including experimental and epidemiological data evaluations [Chan et al, 2000;Hessel et al, 2000;Soutar et al, 2000;Carta et al, 2001;Cocco et al, 2001], the present study provides additional information of interest to further evaluate the association between silica and lung cancer [IARC, 1997;Steenland et al, 2001].…”
Section: Discussionmentioning
confidence: 74%
“…These included studies of ethylene oxide and lymphatic and hematopoietic neoplasms (1), dioxin and all cancers (2), silica and kidney disease (3), cadmium (4), beryllium (5), and diesel fumes and lung cancers (6). At the National Cancer Institute (NCI) one of us (MD) has observed this phenomenon in all three of the studies that he has been involved in that had positive exposure-response findings, which included studies of benzene and lymphopoietic neoplasms (7), silica and lung cancer (8), and acrylonitrile and lung cancer (9). One of us (IHP) has previously reported this phenomenon in her work summarizing six studies of arsenic exposure and lung cancer risk, of which four showed a clear flattening at high exposure levels and two were consistent with either a linear or a supralinear exposure-response pattern (10).…”
mentioning
confidence: 99%
“…A high correlation between exposure to arsenic and exposure to dust or silica (r ¼ 0.82, P ¼ 0.0001) prevented any adjustment of these values during analysis. However, the lung cancer risk was increased only among silicotics exposed to another carcinogen [Cocco et al, 2001] and this helps confirm the role of other lung cancer carcinogens accompanying silica. Further research is needed to understand the complex pattern of interaction between crystalline silica and other lung carcinogens existing in silica mixed dust, which are very prevalent in metal mine industries.…”
Section: Discussionmentioning
confidence: 66%